The Implementation of Bilingual Education in Senior High School in Indonesia - Ersa Ananda Sirait; Hariati Hariati; Wenti Amalia (JURNAL EDUKASI NONFORMAL, 2022)
In Senior High School, bilingual learning is very good to be implemented. The implementation of bilingual education programs in Indonesia's senior high school has seen substantial advances. Since the ISS program was terminated, the phenomena of private schools offering multilingual programs has become much more widespread. The knowledge needed to administer multilingual programs in these schools is lacking, though. The study's goal is to determine how bilingual education is being implemented in senior high schools, particularly in Indonesia. The data was collected by references research by collecting the data from some relevant journal related to bilingual in education in senior high school in Indonesia. A qualitative descriptive approach or a literature review was the method adopted in this research. Where the theories and opinions contained in this study are the results of studies from scientific articles and scientific journals that are relevant to this research. The result shows that, there are three types of bilingual using in senior high school namely ; (1) Full-English, (2) English Dominant and (3) Full- Indonesian.